MXene Ti3C2: An Effective 2D Light-to-Heat Conversion Material - Li, Renyuan; Zhang, Lianbin; Shi, Le; Wang, Peng (ACS nano, 2017)
MXene, a new series of 2D material, has been steadily advancing its applications to a variety of fields, such as catalysis, supercapacitor, molecular separation, electromagnetic wave interference shielding. This work reports a carefully designed aqueous droplet light heating system along with a thorough mathematical procedure, which combined leads to a precise determination of internal light-to-heat conversion efficiency of a variety of nanomaterials. The internal light-to-heat conversion efficiency of MXene, more specifically Ti3C2, was measured to be 100%, indicating a perfect energy conversion. Furthermore, a self-floating MXene thin membrane was prepared by simple vacuum filtration and the membrane, in the presence of a rationally chosen heat barrier, produced a light-to-water-evaporation efficiency of 84% under one sun irradiation, which is among the state of art energy efficiency for similar photothermal evaporation system. The outstanding internal light-to-heat conversion efficiency and great light-to-water evaporation efficiency reported in this work suggest that MXene is a very promising light-to-heat conversion material and thus deserves more research attention toward practical applications.